Die Suchreisen deutscher Trawler 1958 und ihre Ergebnisse - Meyer, A. (1958)
Johann Heinrich von Thunen-Institute, Federal Research Institute for Rural Areas, Forestry and Fisheries began publishing the Informationen aus der Fischereiforschung – Information on Fishery research in 2010